Preventive Efficacy of an Antioxidant Compound on Blood Retinal Barrier Breakdown and Visual Dysfunction in Streptozotocin-Induced Diabetic Rats - Canovai, Alessio; Amato, Rosario; Melecchi, Alberto; Dal Monte, Massimo; Rusciano, Dario; Bagnoli, Paola; Cammalleri, Maurizio (Frontiers in Pharmacology, 2022)
In diabetic retinopathy (DR), high blood glucose drives chronic oxidative stress and inflammation that trigger alterations of the neurovascular balance finally resulting in vascular abnormalities and retinal cell death, which converge towards altered electroretinogram (ERG). In the last years, a growing body of preclinical evidence has suggested that nutrients with anti-inflammatory/antioxidant properties can be able to hamper DR progression since its very early stages. In the present study, we used a streptozotocin-induced rat model of DR, which mimics most aspects of the early stages of human DR, to test the preventive efficacy of a novel compound containing cyanidin-3-glucoside (C3G), verbascoside and zinc as nutrients with antioxidant and anti-inflammatory properties. Western blot, immunofluorescence and electroretinographic analyses demonstrated a dose-dependent inhibition of oxidative stress- and inflammation-related mechanisms, with a significant counterpart in preventing molecular mechanisms leading to DR-associated vasculopathy and its related retinal damage. Preventive efficacy of the compound on dysfunctional a- and b-waves was also demonstrated by electroretinography. The present demonstration that natural compounds, possibly as a consequence of vascular rescue following ameliorated oxidative stress and inflammation, may prevent the apoptotic cascade leading to ERG dysfunction, adds further relevance to the potential application of antioxidants as a preventive therapy to counteract DR progression.